Developing of integral control system of topological elements of optical scales and grids - Гордієнко, Валентин Іванович; Качур, Наталія Володимирівна; Маркіна, Ольга Миколаївна; Маслов, Володимир Петрович (Technology audit and production reserves, 2015)
An integrated approach to creating TV measurement system of geometrical dimensions of topological elements of scales and grids is considered in the article. The main aim is to create and increase the accuracy of measuring television system based on a microscope Biolam to control the geometric dimensions of the topological elements of optical scales and grids. The study was conducted by optical methods and atomic force microscopy. It is developed a technical approach to create an integrated measuring system for technical audit and control of geometric dimensions of topological elements of optical scales and grids. The factors that affect the value of the desired signal are analyzed and the advantages of LED-display as the illuminator in front of the halogen lamp in the developed measuring system are experimentally demonstrated. The experiments on the integrated measuring system using a microscope Biolam and television camera Novus-130 BH allow determining the optimum conditions and reduce the measurement error of topological elements of optical scales and grids by 4,5 % and measure the size of the elements 6-10 microns with an accuracy of ± 0,5 microns. Results of the study can be applied to the optoelectronic enterprises to improve an accuracy of control scales and grids.